Short-eared Owl (Asio flammeus) in the Yucatan Peninsula: the importance of specimens in museum collections - Samuel López de Aquino (Huitzil. Revista Mexicana de Ornitología, 2008)
McAndrews et al. (2006) described the "first fully documented record" of the Short-eared Owl (Asio flammeus) for theMexican state of Yucatan. The apparent absence of the specimen collected by Phillips and Dickerman did not allowconsidering the previous presence of the species in the state of Campeche, however, when we reviewed the collection of theMuseo de las Aves de México we found it. This specimen exemplifies the importance of having voucher specimens inscientific collections.